Enhancing Students' Science Process Skills Through the Use of Virtual Laboratories - Devianti Sandra; Sonia Yulia Friska; Leni Aulia; Rita Romadani (The Future of Education Journal, 2026)
The integration of digital technology into science education has emerged as an effective solution to address the limitations of conventional laboratory facilities in schools. One of the most prominent innovations is the use of virtual laboratories, simulation-based learning environments that enable students to conduct interactive experiments without requiring access to physical laboratories. This study aims to examine how the use of virtual laboratories contributes to the improvement of students' science process skills. A literature review method was employed by analyzing eleven relevant scholarly articles on the implementation of virtual laboratories in science education. The research procedure consisted of problem identification, literature retrieval from various academic sources, selection of relevant references, data analysis, and conclusion drawing. The findings consistently demonstrate that virtual laboratories enhance students' science process skills, particularly in observing, classifying, formulating hypotheses, conducting experiments, analyzing data, and drawing conclusions. Furthermore, the use of virtual laboratories has a positive impact on students' academic achievement, learning motivation, and digital literacy. This study concludes that virtual laboratories are an effective and innovative instructional medium that can serve as a viable alternative to conventional laboratories for improving the quality of science education in schools.